Community water demand and sustainable water supply planning in Nigeria : a review - Ezugwu, Charles; Onyelowe, Kennedy; Ezugwu, Chisom; Onyekweredike, Kelechi; Odumade, Adegboyega; Omunakwe, Okechukwu; Hussaini, Mahmud; Oloyede, Amodu; Innocent, Wokocha (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this study is to review past works in water demands and sustainable water supply planning in Nigeria as reported by many researchers and to determine how to improve the water supply infrastructure sustainably. Nigeria is endowed with abundant surface water and ground water resources. The mean annual rainfall along the coast in the south east is 4 800 mm while it is less than 500 mm in the north east. These water sources are not tapped to the fullest and most of them are polluted and unsafe for use, resulting to scarcity of potable water in most communities. Water crisis is prevalent in most cities and this is further exacerbated by deteriorating infrastructure, political instability, and poorly regulated water laws. The result of the water crisis has led to detrimental consequences for its citizens as child mortality and water-borne disease-related deaths have grown exponentially. Unsuitability of water distribution facilities, quantity of water transported, too much walking distance, long lines at water points, poor maintenance and inadequate bulk water development brought about inefficiency of the facility. The water demand and supply in some countries in the world and many towns in Nigeria were reported. The method adopted in the study involved the use of journals, books and other related literature. The result showed that water supply systems in most places in the country are in poor state, unorganized and incomplete. All countries highlighted showed many problems at various degrees in provision of the facility. Attempt was made to fill some gaps in the literature. Public enlightenment, financing, monitoring, maintenance and juicy annual remuneration packages for best water users are recommended as powerful tools towards sustenance of the water supply infrastructure.